SIZE AT FIRST MATURITY OF THE BLUE SPOTTED MASKRAY, Neotrygon kuhli lN INDONESIAN, WATERS - Fahmi Fahmi; Mohammad Adrim; Dharmadi Dharmadi (Indonesian Fisheries Research Journal, 2009)
The biue spotted maskray, Neotrygon kuhtii is the most common rays occurred in Indonesian waters. This species is often caught as bycatch in trawl fisheries targeting demersal fishes and shrimps.